Treatment of Postherpetic Neuralgia Using a Thoracic Transforaminal Epidural Steroid Injection. Issue 4 (2nd December 2014) - Mehta, Priyesh; Maher, Patrick; Singh, Jaspal Ricky
Abstract: A 64‐year‐old male patient with a history of herpes zoster exposure presented with severe, constant, burning pain in the left T10 dermatome consistent with postherpetic neuralgia. Previous treatment included oral and topical medications as well as an intercostal nerve block; however, these treatment options did not provide significant relief. The patient was treated with a single‐level T10 thoracic transforaminal epidural steroid injection for refractory postherpetic neuralgia. He reported complete resolution of his symptoms at 2‐ and 12‐week follow‐ups. This case illustrates transforaminal epidural steroid injections may be a successful treatment option for postherpetic neuralgia.